Repeated dosing of myrrh, chamomile extract, and coffee charcoal reveals potential health-beneficial effects in patients with irritable bowel syndrome in the M-SHIME simulator - Meinolf Wonnemann; Bartosz Lipowicz; Cindy Duysburgh; Chloë Rotsaert; Lynn Verstrepen; Massimo Marzorati; Jost Langhorst (PLoS ONE, 2026)
Objective To define the potential functional roles of a herbal preparation of myrrh, chamomile extract, and coffee charcoal in patients suffering from diarrhea dominant irritable bowel syndrome (IBS-D). Methods The study utilized the Mucosal Simulator of the Human Intestinal Microbial Environment (M-SHIME ® ) with proximal (PC) and distal colon (DC) compartments and fecal samples from four IBS-D donors. Eight-day (d) repeated dosing with the herbal product (6 tablets/day) was initiated compared to a negative control. Changes in microbial metabolism and community composition were assessed, and colonic ferments were evaluated for their effects on intestinal barrier permeability and cytokine production in a Caco-2/THP-1 co-culture model. Results Product treatment significantly increased gas pressure versus negative control, indicating microbial fermentative activity. Product supplementation significantly increased proximal acetate (d3, d5), propionate (d3), and butyrate (d5, d8) levels (p < 0.05 for all), while no significant changes were observed distally. Ammonium levels were significantly elevated following product supplementation in PC (d3, d5, d8; p < 0.05) and DC (d8; p < 0.01), though remained within physiological range. Repeated dosing enriched members of Bifidobacteriaceae , Bacteroidota, Lachnospiraceae , and Butyricicoccus versus negative control. Treated colonic ferments had a protective effect on intestinal membrane integrity (DC; p < 0.001) and positive immunomodulatory effects (increased IL-10, PC and DC [both p < 0.0001], and IL-6, PC [p < 0.001] and DC [p < 0.01]) in Caco-2/THP-1 co-cultures. Conclusions Treatment with a herbal preparation of myrrh, chamomile extract, and coffee charcoal showed a potential beneficial effect on the microbiota of patients with IBS-D in vitro , suggesting further exploration of its efficacy in IBS-D and other chronic gastrointestinal disorders.